2017
DOI: 10.1016/j.stemcr.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning of Human Pluripotent Stem Cell-Derived Engineered Cardiac Tissue Contractility for Automated Drug Classification

Abstract: SummaryAccurately predicting cardioactive effects of new molecular entities for therapeutics remains a daunting challenge. Immense research effort has been focused toward creating new screening platforms that utilize human pluripotent stem cell (hPSC)-derived cardiomyocytes and three-dimensional engineered cardiac tissue constructs to better recapitulate human heart function and drug responses. As these new platforms become increasingly sophisticated and high throughput, the drug screens result in larger multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Animal studies for drug testing often mislead drug development processes due to genotypic and physiological differences between species . As a substitute for the current in vitro and in vivo models, several studies have suggested using 3D cardiac organoids as a new model system to check cardiac responses to drugs by demonstrating that the organoids enable evaluation of well‐known drugs, such as verapamil, isoproterenol, and metoprolol . For example, Agarwal et al.…”
Section: Current Progress In Organoid Technologiesmentioning
confidence: 99%
“…Animal studies for drug testing often mislead drug development processes due to genotypic and physiological differences between species . As a substitute for the current in vitro and in vivo models, several studies have suggested using 3D cardiac organoids as a new model system to check cardiac responses to drugs by demonstrating that the organoids enable evaluation of well‐known drugs, such as verapamil, isoproterenol, and metoprolol . For example, Agarwal et al.…”
Section: Current Progress In Organoid Technologiesmentioning
confidence: 99%
“…To overcome those limitations, small size EHT platforms have been described in the literature, including the Heart-Dyno platform [ 98 , 102 ], the Cardiac MicroRings (CaMiRi) [ 87 ] and the µTUG arrays [ 95 ]. Some platforms are now commercially available, such as in the case of the Biowire TM II platform (TARA Biosystems) [ 94 , 117 ] and the cardiac tissue strip model (Novoheart TM ) [ 127 , 128 ] (see Table 2 ).…”
Section: In Vitro Applications Of Hpsc-derived 3d Cardiac Microtismentioning
confidence: 99%
“…The selected parameters should reflect relevant changes related to the pharmacological effects and preferentially allow the discrimination of different levels of toxicity severity and different types of toxic effects [ 138 , 139 ]. In addition to the development and selection of the best methodologies to capture and quantify the effects of cardioactive compounds on hPSC-CMs, the development of strategies that help in the identification and interpretation of the readouts in order to define which type of cardiotoxicity is associated with a specific compound and elucidate the mechanism of action is also a relevant topic that should be taken into consideration [ 128 ].…”
Section: In Vitro Applications Of Hpsc-derived 3d Cardiac Microtismentioning
confidence: 99%
“…Approaches that incorporate the randomization of in silico parameters, non-linear modelling and chaos theory [63] together with the application of machine learning tools [64] and self-correcting parameterization [33] may lead to a better representation of 'real world' scenarios. Drug development will also benefit from input data acquired from a broader palette of studies performed in humans e.g.…”
Section: Defining the Physiological Gamut And Systems Limitsmentioning
confidence: 99%